2017
DOI: 10.1371/journal.pone.0170561
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pulmonary Fibrosis in a Bleomycin Mouse Model Using Automated Histological Image Analysis

Abstract: Current literature on pulmonary fibrosis induced in animal models highlights the need of an accurate, reliable and reproducible histological quantitative analysis. One of the major limits of histological scoring concerns the fact that it is observer-dependent and consequently subject to variability, which may preclude comparative studies between different laboratories. To achieve a reliable and observer-independent quantification of lung fibrosis we developed an automated software histological image analysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…OA administration exerted similar to IT administration functional impairment on respiratory mechanics compared to saline-treated controls, as assessed by significant reductions in: (1) static lung compliance ( Cst ), (2) respiratory system compliance ( Crs ), and (3) total lung capacity ( A ), as well as increases in: (4) respiratory system elastance ( Ers ), (5) tissue elastance ( H ), (6) curvature of the upper portion of the deflation limb of the PV curve ( K ), (Figure 1D ). Both static and dynamic lung compliance as well as elastance and total (inspiratory) lung capacity were found to be reliable indices of fibrotic lung injury, as recently suggested ( 18 ), well correlating with the Ashcroft score (Table S1 ). Therefore, and as the method is the most relevant to clinical measurements in human patients, not requiring additional mouse numbers, it is thus proposed as a valuable surrogate analysis of BLM-induced pulmonary fibrosis.…”
Section: Resultssupporting
confidence: 75%
“…OA administration exerted similar to IT administration functional impairment on respiratory mechanics compared to saline-treated controls, as assessed by significant reductions in: (1) static lung compliance ( Cst ), (2) respiratory system compliance ( Crs ), and (3) total lung capacity ( A ), as well as increases in: (4) respiratory system elastance ( Ers ), (5) tissue elastance ( H ), (6) curvature of the upper portion of the deflation limb of the PV curve ( K ), (Figure 1D ). Both static and dynamic lung compliance as well as elastance and total (inspiratory) lung capacity were found to be reliable indices of fibrotic lung injury, as recently suggested ( 18 ), well correlating with the Ashcroft score (Table S1 ). Therefore, and as the method is the most relevant to clinical measurements in human patients, not requiring additional mouse numbers, it is thus proposed as a valuable surrogate analysis of BLM-induced pulmonary fibrosis.…”
Section: Resultssupporting
confidence: 75%
“…It has been reported that BLM administered intratracheally to induce PF can reduce body weight while increasing lung weight, although these changes can be improved with suitable medication (13). Lung weight increases in proportion to the dose of intratracheally administered BLM, and the increased lung weight is associated with histopathological fibrosis scores (14).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination of the lungs performed 20 weeks post-irradiation showed collagen deposition, as detected by the saffron (yellow) staining (figure 2e) and sirius red staining (online supplementary figure S1a) in irradiated lungs. Quantitative assessment of parenchymal fibrosis using automated histological image analysis software [18] showed a significant FIGURE 3 Inflammatory cell characterisation during thoracic radiation-induced injury. a) Fold increase of number of interstitial neutrophils within parenchyma during radiation injury in nonirradiated and irradiated C57BL/6 mice; b) gating strategy to identify neutrophils (Neutr; Gr1 + CD11b + ) and monocytes (Mono; Gr1 inter CD11b + ) within parenchyma of nonirradiated and irradiated mice 20 weeks after irradiation; c) fold increase of neutrophil number in bronchoalveolar lavage (BAL) during radiation injury in irradiated and nonirradiated mice; d) gating strategy to identify neutrophil (Gr1 high CD11b + ) and monocytes (Gr1 + CD11b + ) in BAL of nonirradiated and irradiated mice 20 weeks after irradiation; e) fold increase of number of interstitial monocytes within parenchyma during radiation injury in irradiated and nonirradiated mice; f) fold increase of monocyte number in BAL during radiation injury in irradiated and non-irradiated mice; g) fold increase in number of alveolar macrophages (AMs) during radiation injury in irradiated and nonirradiated mice; h) gating strategy to identify AMs (CD11c + CD11b − ) in nonirradiated and irradiated mice 20 weeks after radiation; i) fold increase of number of tissue-infiltrating macrophages (IMs) during radiation injury in irradiated and nonirradiated mice; j) gating strategy to identify IMs (F4/80 + Gr1 − ) in nonirradiated and irradiated mice 20 weeks after irradiation.…”
Section: Rif Is Associated With An Accumulation Of Pulmonary Macrophagesmentioning
confidence: 99%